No translation is better than a bad translation - Husić, Snježana (2005)
The experience of Zagreb-based Festival of European Short Story and its Translation Workshops are seen as an example of alternative literary and linguistic policy, especially in the field of translation, aimed to preserve peculiar characters of "small" literatures and languages.
Projekt MZOS
ENG